كفاءة الشعّيّات المعزولة من بحيرتي قطينة وسد الروم في النمو في الأوساط الملوثة بالجفت والنفط الخام - نظام, عدنان; عايد, هنادي (Latakia University Journal -Biological Sciences Series, 2017)
يمتلك العديد من الجراثيم القدرة على المعالجة الحيوية للملوثات العضوية في البيئة المائية بما يمتلكه من مقدرة عالية على إنتاج الإنزيمات، ومن أهم هذه الملوّثات الجفت الناتج عن عصر الزيتون بسبب احتوائه مركبات فينولية، والنفط الخام الناتج عن حوادث التسرّب المتكررة بسبب صعوبة تفككه وقدرته على البقاء طويلاً، والتأثير السام لهذه الملوثات في البيئة، وهي من أكثر المشكلات البيئية حساسية واستمرارية في سورية. اختُبرت في هذا البحث مقدرة الشعّيات المعزولة محلياً على النمو في الأوساط السائلة الملوثة بالجفت والنفط الخام بعد عزلها من بحيرتي قطينة وسد الروم، وتعريفها، على مدى ثلاثة أسابيع من خلال تغير الكثافة الضوئية والتعداد الكلي للجراثيم والرقم الهدروجيني pH في الوسط السائل الحاوي الملوّث العضوي والسلالة المختبرة. إذ تم تعريف 9 سلالات تنتمي إلى أجناس الشعيَّات الآتية:Streptomyces (S1, S2, S3, S4, S5) و Micromonospora (M7, M8, M9)و Nocardia (N6)بعد تحديد صفاتها المورفولوجية والحيوية الكيميائية، حيث أبدى معظم هذه السلالات المعزولة مقدرة على النمو على الأوساط الصلبة الحاوية الجفت والنفط الخام، كما تبين بأن قدرة السلالات المنتخبة على النمو في الأوساط السائلة الملوثة بالنفط الخام كانت أقل مقارنةً بنموها في تلك الحاوية الجفت ولاسيما في الأسبوع الثالث من الحضن، مع ملاحظة وجود انخفاض في قيم pH، وازدياد الكثافة الجرثومية في جميع الأوساط السائلة المختبرة مع زيادة فترة الحضن، مما يؤكد على أن هذه السلالات المعزولة قد تكون فعالة في عملية المعالجة الحيوية لهذين الملوثين. Many of bacteria have the ability to bioremediation organic contaminants in the aquatic environment because of their ability to produce many enzymes. Olive Mill Waste Water OMWW is one of the most important pollutant because its phenolic compounds, and crude oil resulting from repeated spill incidents revealed difficulty to decomposition, accumulate for long time, and toxicity effects, that make these two pollutants the most sensitivity and continuity environmental problems in Syria.Many of local Actinobacteria strains were tested in this study for their ability to grow in liquid media contains OMWW and crude oil for three weeks, after isolated from Quttaineh and Roman bridge lakes and characterized, by detected the changes of optical density, total viable count and pH value in liquid medium containing organic pollutant and tested strain. After determination the morphological and biochemical characteristics, 9 strains of Actinobacteria were defined as following genera: Streptomyces (S1, S2, S3, S4, S5), Micromonospora (M7, M8, M9) and Nocardia (N6), most of these strains were revealed ability to grow on solid media contain OMWW and crude oil, although selected strains were revealed ability to grow in liquid media polluted by crude oil were lower compared to their growth in that polluted by OMWW especially in the third week of incubation, with a decrease in pH values and increase in bacterial density, when the incubation period increased for all detected liquid media, which emphasizes that these isolates may be effective in the bioremediation of these pollutants.